Low Incidence of Advanced Neoplasia in Serrated Polyposis Syndrome After (Sub)total Colectomy: Results of a 5-Year International Prospective Cohort Study. (9th August 2019) - Bleijenberg, A.G.C.; IJspeert, J.E.G.; Carballal, S.; Pellise, M.; Jung, G.; van Herwaarden, Y.J.; Bisseling, T.M.; Nagtegaal, I.D.; van Leerdam, M.E.; Spaander, M.C.W.; van Lelyveld, N.; Bessa, X.; et al.
Abstract : INTRODUCTION: Serrated polyposis syndrome (SPS) is accompanied by a substantially increased colorectal cancer (CRC) risk. To prevent or treat CRC in patients with a very high polyp burden, (sub)total colectomy with ileorectal or ileosigmoidal anastomosis is regularly performed. The CRC risk after (sub)total colectomy might be decreased, but evidence is lacking. We aimed to assess the yield of endoscopic surveillance in patients with SPS who underwent (sub)total colectomy. METHODS: For this post hoc analysis, we used prospectively collected data from a large international prospective cohort study. We included patients diagnosed with SPS (World Health Organization type I and/or III) who underwent (sub)total colectomy. Primary endpoint was the cumulative 5-year incidence of CRC and advanced neoplasia (AN). RESULTS: Forty-eight patients (mean age 61 [±7.8]; 52% men) were included and followed up for a median of 4.7 years (interquartile range 4.7–5.1). None of the patients developed CRC during follow-up. Five patients developed AN, corresponding to a cumulative 5-year AN incidence of 13% (95% confidence interval 1.2–23). In 4 patients, AN was diagnosed at the first surveillance endoscopy after study inclusion, and in 1 patient, AN was detected during subsequent rounds of surveillance. The risk of AN was similar for patients with ileorectal and ileosigmoidal anastomosis (logrank P = 0.83). DISCUSSION: (Sub)total colectomy mitigates much of the excess risk of CRC in patients with SPS. Advanced neoplasms are mainly detected at the first endoscopy after (sub)total colectomy. Based on these results, after the first surveillance, intervals might be extended beyond the currently recommended 1–2 years.